(3bdGFO GdYbjGf heMGSf GdQDSGA h GdbVGI hGdcJGH hGdCeQGA GdCYjGfs - (3CHi fUQ GdaJM Hf eMeO Hf YHjO Gddg Hf NGbGf GdbjSi GdETHjdi,J (B528 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi QGVi dfG GdHjGf MJi EfbGO ai CYfJfG s
(3BNQgG (B:s
(3CKfGA JQLeI CHj HcQ Hf HGLI s
(3GfXQ HQbe (B" 385" (3HQbe (B" 1175" (3JGQjNs
(3fSNI NGeSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B134 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B49s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B328 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs